(3GdefGRYGJ GdLeQcjI aj VhA Gdabg hGLJgGO GdbVGA hGdLOjO aj bGfhf GdLeGQcs - (3CMSf(B, (3HhSbjYIs ((3GdLRGFQ(B:s (3OGQ GdMceI ddfTQ(B,s, 1997)
(3GdJLQje(B- (3eYGjfI GdLQGFe heJGHYJgG(B- (3beY GdLQGFe GdEdcJQhfjI(B- (3eSDhdjI GdCTNGU Yf GdLQGFe GdLeQcjI(B- (3GdeSDhdjI GdeOjfI(B- (3GdJVGefs
Keywords: (3GdLeGQcs; (3GdefGRYGJs